Gerindra Party's Political Marketing Strategy in Increasing Vote Acquisition in the 2024 Legislative Elections in East Java - Az-zahra, Tsanaa Shofiyyah; Suwarko, Andi; Ridha Amaliyah (JURNAL TAPIS, 2026)
This study analyzes the political marketing strategy of the Gerindra Party in increasing East Java Provincial Parliament (DPRD) seats from 15 to 21 (40 percent) in the 2024 General Election, and identifies key determinants of its electoral success. A qualitative case study design was employed, with data from in-depth interviews with 12 informants comprising party executives, legislative candidates, campaign teams, and voters from four sub-cultural regions of East Java (Arek, Madura, Mataraman, and Tapal Kuda), supplemented by observation and documentation, analyzed using Miles and Huberman’s interactive model. The findings reveal that Gerindra applied eight integrated stages of the Market Oriented Party (MOP) framework, with three proving most determinant: the coattail effect of Prabowo Subianto, who secured 65 percent of East Java’s presidential votes; sub-cultural product adaptation across the four regions; and the mobilization of 100,000 trained witnesses supported by a real-time digital monitoring system. Total campaign expenditure reached Rp45 billion at the provincial board level and Rp2–4 billion per candidate. Patronage and clientelism were adaptively integrated within the MOP framework as complementary mobilization mechanisms. This study concludes that Gerindra’s electoral success resulted from the adaptive integration of modern political marketing with patronage-clientelism, calibrated to the socio-cultural characteristics of each sub-region. Theoretically, this study shows that the Political Market-Oriented Approach must be understood alongside patronage dynamics as a structural feature of Indonesian electoral democracy